1
$\begingroup$

If $\theta$ represents an angle such that $\sin(2\theta) = \tan(\theta) - \cos(2\theta)$, then $\sin(\theta) - \cos(\theta)=$...?

I've been trying to do this problem for a while, but for some reason, I haven't been able to get the answer. I rewrote the $\sin(2\theta)$ as $2\sin(\theta)\cos(\theta)$ and $\tan(\theta) = \sin(\theta)/\cos(\theta)$ and $\cos(2\theta) = \cos^2(\theta) - \sin^2(\theta)$ since there are both sines and cosines here, and I've tried a few other manipulations, but I don't know what to do from then on.

$\endgroup$
1
$\begingroup$

We have $$\sin(2\theta) = \tan(\theta) - \cos(2\theta)$$ so $$2\sin \theta\cos\theta=\frac{\sin\theta}{\cos\theta}-1+2\sin^2\theta$$ $$2\sin\theta\cos^2\theta=\sin\theta-\cos\theta+2\sin^2\theta\cos\theta$$ Hence $$\sin\theta-\cos\theta=2\sin\theta\cos\theta(\cos\theta-\sin\theta)=-\sin2\theta(\sin\theta-\cos\theta)$$giving $$(1+2\sin2\theta)(\sin\theta-\cos\theta)=0$$ So either $$\sin\theta-\cos\theta=0$$ or $$\sin2\theta=-\frac12\implies \theta=k\pi-\frac\pi{12}$$ for $k\in\mathbb{Z}$ thus $$\sin\theta-\cos\theta=\pm\frac{\sqrt6}2$$ (consider the cases when $k$ is even and odd)

Therefore $$\boxed{\sin\theta-\cos\theta=-\frac{\sqrt6}2, 0, \frac{\sqrt6}2}$$

$\endgroup$
2
$\begingroup$

Hint:

Using The Weierstrass Substitution,

$t=\tan\theta,$

$$2t+1-t^2=t(1+t^2)\iff0=t^3+t^2-t-1=t^2(t+1)-(t+1)=(t+1)^2(t-1)$$

$\implies t=\pm1$

$\endgroup$
1
$\begingroup$

You have $$ \sin2\theta-\tan\theta=-\cos2\theta $$ The left-hand side is $$ 2\sin\theta\cos\theta-\tan\theta=2\tan\theta\cos^2\theta-\tan\theta= \tan\theta(2\cos^2\theta-1)=\tan\theta\cos2\theta $$ so the equation becomes $$ \cos2\theta(1+\tan\theta)=0 $$ Can you finish?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.